Mango sheets from vacuum dehydration of the puree - Arcellana, Mayi Y.
Mango sheets were developed by vacuum drying the pasteurized puree. The puree was characterized in terms of moisture content, titratable acidity, soluble solids, soluble solids/titratable acidity ratio, and reducing sugars content. Drying of pure pasteurized puree under different conditions of temperature and final moisture content was undertaken. Results of the objective and sensory evaluations revealed that it would be best to produce pure fruit mango sheets by drying at 70°C to 20% moisture. The drying of sweetened and unsweeetened purees to about 20% moisture was done. Based on the results of the objective and sensory evaluations, the best mango sheet was produced from puree sweetened to 8% by weight by drying at 70°C to 20% moisture